Birth of an icon Frank Gehry's disney hall - Films for the Humanities & Sciences (New Jersey : Films for the Humanities & Sciences, 2004)
In this segment, Frank Gehry comments on how he designed the concert hall using 3-D computer modeling, while the Philharmonic's executive director and two musicians extol the virtures of master acoustician Yasuhisa Toyota's efforts.
Videodisc release of a segment of the television program The news hour with Jim Lehrer.
DVD format.
Keywords: Gehry, Frank O., -- 1929-.; Architecture, American -- California -- Los Angeles; Music-halls -- California -- Los Angeles